Copper-mediated oxidative [3 + 2]-annulation of nitroalkenes and pyridinium ylides: general access to functionalized indolizines and efficient synthesis of 1-fluoroindolizines. Issue 6 (23rd January 2019) - Motornov, Vladimir A.; Tabolin, Andrey A.; Nelyubina, Yulia V.; Nenajdenko, Valentine G.; Ioffe, Sema L.
Abstract : Novel 1-fluoroindolizines were obtained via copper(ii )-mediated oxidative [3 + 2]-annulation of in situ generated pyridinium ylides and fluoronitroalkenes. Abstract : A general method for the synthesis of substituted indolizines by copper(ii ) acetate-promoted oxidative [3 + 2]-annulation of α-fluoronitroalkenes with in situ generated pyridinium ylides was developed. Application of the copper(ii ) acetate–2, 6-lutidine system provides efficient access to various 1-fluoroindolizines in up to 81% yield. Both electron-rich and electron-deficient nitroalkenes as well as different pyridinium and isoquinolinium salts can be involved in the reaction. Moreover, it was found that copper-mediated annulation is applicable for other α-substituted (alkyl, chloro, and ester) nitroalkenes giving rise to the corresponding indolizines. First synthesis of monofluorinated [3, 2, 2]cyclazines was demonstrated via oxidative annulation of 3-unsubstituted fluoroindolizines with diethyl acetylene dicarboxylate.